2019
DOI: 10.14720/aas.2019.113.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Seed yield of two new quinoa (Chenopodium quinoa Willd.) breeding lines as affected by sowing date in Central Italy

Abstract: <p>Research on the introduction of quinoa in Italy is currently lacking. The present research was aimed at identifying the correct sowing period. Field experiment was consucted in Cesa, Tuscany, in 2017. Two new breeding lines coded as DISPAA-Q42 and DISPAA-Q47-CB were utilized. Three sowing dates (SD) were implemented: February 23; March 17 and April 27. Results showed that the most successful SD was February 23. A significant decrease in both seed yield and a delay in phenological phases, relating to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
3
2
0
3
Order By: Relevance
“…However, late sowing decreased these parameters. Similar results were found in central Italy by [6], where high levels of temperature and photoperiod of late sowing decreased the number of days after emergence to panicle appearance and flowering. In other studies, late sowing also decreased the vegetative development of quinoa and resulted in stunted plants [5,7].…”
Section: Discussionsupporting
confidence: 84%
“…However, late sowing decreased these parameters. Similar results were found in central Italy by [6], where high levels of temperature and photoperiod of late sowing decreased the number of days after emergence to panicle appearance and flowering. In other studies, late sowing also decreased the vegetative development of quinoa and resulted in stunted plants [5,7].…”
Section: Discussionsupporting
confidence: 84%
“…Quinoa is generally cultivated for its seeds which are utilized as human food. Thus, a great majority of agronomic studies conducted on the plant includes evaluations on seed performance (Geren et al, 2014;Kir and Temel, 2016;Kir and Temel, 2017;Tan and Temel, 2017a;Tan and Temel, 2018;Casini, 2019). In the studies carried out, it was revealed that seed performances were significantly affected by sowing and harvesting periods and, as a consequence, sowing or harvesting should be carried out at an early or late period (Risi and Galwey, 1991;Aguilar and Jacobsen, 2003;Munir, 2011;Geren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, en Egipto, el mildiu afectó el rendimiento de la variedad "Negro" y "Rainbow" en un 95 y 87 %, respectivamente (Ahmed & Abdel-Wahed, 2018). Se demostró que el día de siembra es un factor importante para calcular el rendimiento de las plantas (Casini, 2019). No obstante, la aplicación de ecofungicidas ocasionó que el rendimiento no se viera tan afectado, lo cual se evidenció en la variedad "Blanca Junín" (Estrada Zúñiga et al, 2022).…”
Section: Rendimiento Por Hectáreaunclassified
“…Un estudio determinó, al evaluar el rendimiento por hectárea de las variedades estudiadas, la importancia del día de la siembra, porque este factor es determinante al calcular el rendimiento real de las plantas (Casini, 2019).…”
Section: Rendimiento Por Hectáreaunclassified